Effect of Bacillus subtilis isolated from yaks on D-galactose-induced oxidative stress and hepatic damage in mice - Wang, Lei; Li, Aoyun; Zhang, Xiaohu; Iqbal, Mudassar; Aabdin, Zain Ul; Xu, Mengen; Mo, Quan; Li, Jiakui (Frontiers in Microbiology, 2025)
Acute hepatic injury is a severe condition that is always accompanied by oxidative stress and inflammation, seriously threatening the health of the host. Probiotics have been shown to be involved in the regulation of antioxidant system and gut microbiota activity, but studies on the effects of yak derived Bacillus subtilis (B. subtilis) on acute liver injury and oxidative stress remain scarce. Here, we aim to explore the ameliorative effects of B. subtilis isolated from yaks on oxidative stress and hepatic injury caused by D-galactose, as well as the underlying processes. Results indicated that B. subtilis administration, particularly the BS3, significantly mitigated hepatic damage induced by D-galactose in mice as evidenced by ameliorating liver tissue damage as well as decreasing ALT (p < 0.05) and AST (p < 0.05) levels. Additionally, the B. subtilis intervention was demonstrated to enhance the antioxidant system in D-galactose-exposed mice, as manifested by increased T-AOC and SOD, alongside a decrease in MDA levels (p < 0.05). Meanwhile, B. subtilis intervention could effectively mitigate oxidative damage via modulating the Keap1/Nrf2 signaling pathway. Importantly, B. subtilis exhibited a pronounced protective effect against D-galactose-induced intestinal barrier dysfunction through improving tight junction proteins. The gut microbiota results suggest that BS3 alters the abundance of some gut flora such as Firmicutes phylum and Oscillibacter and Lachnospiraceae_NK4A136 genera, which affects the composition of the gut microbiota and reverses the decrease in the microbial richness index in mice. In summary, these findings demonstrated that B. subtilis isolated from yaks serve as a promising candidate to ameliorate oxidative damage and hepatic injury. Meanwhile, the positive regulation effect of B. subtilis on gut microbiota and intestinal mucosal barrier may be one of its underlying mechanisms to alleviate oxidative stress and hepatic injury.